2017
DOI: 10.1159/000471938
|View full text |Cite
|
Sign up to set email alerts
|

Triiodothyronine Potentiates Vasorelaxation via PKG/VASP Signaling in Vascular Smooth Muscle Cells

Abstract: Background/Aims: Vascular relaxation caused by Triiodothyronine (T3) involves direct activation of endothelial cells (EC) and vascular smooth muscle cells (VSMC). Activation of protein kinase G (PKG) has risen as a novel contributor to the vasorelaxation mechanism triggered by numerous stimuli. We hypothesize that T3-induced vasorelaxation involves PKG/vasodilator-stimulated phosphoprotein (VASP) signaling pathway in VSMC. Methods: Human aortic endothelial cells (HAEC) and VSMC were treated with T3 for short (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 45 publications
(48 reference statements)
4
25
0
1
Order By: Relevance
“…T3 Activates PKG/VASP Signaling in the Aortas of HS-Treated Rats. Based on our previous study showing that T3 promotes vascular relaxation via a PKG/VASP signaling pathway in cultured vascular smooth muscle cells (VSMC) (Samuel et al, 2017), we examined whether improvement of function in hypertensive aortas caused by short-term treatment with T3 is associated with activation of PKG/VASP signaling. The immunoblot analysis revealed that expression of PKG in aortas from the HS group was significantly reduced in comparison with the LS group (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…T3 Activates PKG/VASP Signaling in the Aortas of HS-Treated Rats. Based on our previous study showing that T3 promotes vascular relaxation via a PKG/VASP signaling pathway in cultured vascular smooth muscle cells (VSMC) (Samuel et al, 2017), we examined whether improvement of function in hypertensive aortas caused by short-term treatment with T3 is associated with activation of PKG/VASP signaling. The immunoblot analysis revealed that expression of PKG in aortas from the HS group was significantly reduced in comparison with the LS group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The aortas were treated with 0.1 mM T3 (Sigma-Aldrich) for 30 minutes. The concentration of T3 was chosen based on results from a previous study (Samuel et al, 2017). A stock solution of T3 was made by dissolving T3 in DMSO (ATCC) and further diluted in Krebs solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mass spectrometry on STZ-induced diabetic rats showed high levels of lysine-acetylated proteins in their kidney cells compared to control animals (Kosanam et al, 2014 ). Also, treatment of murine aorta cells with high glucose or FFA to induce short term diabetes causes increased levels of lysine acetylation (Samuel et al, 2017 ). Although, there are very few reports, aberrant acetylation of tau in T2DM may interfere with the physiological functions of microtubule binding and assembly predisposing cytoplasmic tau toward the formation of aggregates (Irwin et al, 2013 ; Trzeciakiewicz et al, 2017 ).…”
Section: Crosstalk Of T2dm and Tau Pathology In Admentioning
confidence: 99%